Therapeutic Potential of Biomineralization‐Based Engineering. Issue 8 (23rd August 2018) - Wang, Xiaoyu; Xiao, Yun; Hao, Haibin; Zhang, Ying; Xu, Xurong; Tang, Ruikang
Abstract: In nature, the biomineralization processes of living organisms produce a wide range of organic–inorganic hybrid materials to achieve various functions. In particular, egg shells can provide extra protection for embryos and maintain air exchange. Inspired by such phenomena, it is assumed that the engineering of organisms with biomimetic materials can lead to significant improvement in organism function. This review summarizes recent progress in biomineralization‐based techniques for organism engineering, and demonstrates the therapeutic potential enabled by these techniques. The design and synthesis approaches of biomineralization‐based engineering are systemically introduced to guide the controlled modification of different organisms including viruses, bacteria, cells, and proteins using in situ biomineralization, bottom‐up self‐assembly, chemical and genetic engineering. Tailored organisms promise delivery, protection, cell therapy, vaccine improvement as well as therapeutic detection and imaging. The present review aims to propose a biomineralization‐based strategy to promote functional evolution of these organisms, which promises to meet the increasing demand for new therapeutic purpose. Abstract : Inspired by the naturally occurring biomineralization processes, it is assumed that the engineering of organisms with a biomimetic mineral structure can lead to significant functional improvement and evolution of organisms. This review summarizes the recent progress in biomineralization‐based engineering and its therapeutic potential.